Relationship between professional training and performance in pre-professional practice (internship) of students of the IX and X cycle of the Nursing Career of the Universidad Privada de Huancayo Franklin Roosevelt - Suasnabar Cueva, Edith (2020)
The objective of this research was to determine the relationship that exists between professional training and the performance in pre-professional practice of students in the IX and X semesters of the Nursing Career at the Private University of Huancayo Franklin Roosevelt. It was concluded that there is no significant relationship between professional training and performance in pre-professional practice (Internship) of students of the IX and X semesters of Nursing Career at the Private University of Huancayo Franklin Roosevelt.